Atlas of Ocular Optical Coherence Tomography (Springer International Publishing, 2018)
This book provides a collection of optical coherence tomographic (OCT) images of various diseases of posterior and anterior segments. It covers the details and issues of diagnostic tests based on OCT findings which are crucial for ophthalmologists to understand in their clinical practice. Throughout the chapters all aspects of this non-invasive, popular imaging technique, known for ingenuity and accuracy, is clearly illustrated. Atlas of Ocular Optical Coherence Tomography has been categorized into eleven sections, discussing and illustrating distinct OCT features, as well as showing other image modalities such as fluorescein angiography, fundus autofluorescence, perimetry and laboratory examination. This book also covers choroidal pathologies and vitreous abnormalities. The last section has been allocated to anterior segment disease, including cornea, angle, iris and conjunctival abnormalities. Above all, the numerous images, and detailed descriptions of diseases, make this book an essential guide for general ophthalmologists and ophthalmology residences.